Cellobiose dehydrogenase in biofuel cells. (February 2022) - Scheiblbrandner, Stefan; Csarman, Florian; Ludwig, Roland
Graphical abstract: Abstract : Enzymatic biofuel cells utilize oxidoreductases as highly specific and highly active electrocatalysts to convert a fuel and an oxidant even in complex biological matrices like hydrolysates or physiological fluids into electric energy. The hemoflavoenzyme cellobiose dehydrogenase is investigated as a versatile bioelectrocatalyst for the anode reaction of biofuel cells, because it is robust, converts a range of different carbohydrates, and can transfer electrons to the anode by direct electron transfer or via redox mediators. The versatility of cellobiose dehydrogenase has led to the development of various electrode modifications to create biofuel cells and biosupercapacitors that are capable to power small electronic devices like biosensors and connect them wireless to a receiver.